2016
DOI: 10.1021/acs.nanolett.6b04296
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Film-Over-Nanosphere Substrates for Deep-UV Surface-Enhanced Resonance Raman Spectroscopy

Abstract: We report here the first fabrication of aluminum film-over nanosphere (AlFON) substrates for UV surface-enhanced resonance Raman scattering (UVSERRS) at the deepest UV wavelength used to date (λ = 229 nm). We characterize the AlFONs fabricated with two different support microsphere sizes using localized surface plasmon resonance spectroscopy, electron microscopy, SERRS of adenine, tris(bipyridine)ruthenium(II), and trans-1,2-bis(4-pyridyl)-ethylene, SERS of 6-mercapto-1-hexanol (as a nonresonant molecule), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 43 publications
2
80
0
Order By: Relevance
“…Wang et al [45] reported a lifetime reduction of ≈7.2×, exceeding the previously reported value ≈3.5× by Jiao et al [44]. The first fabrication of Al film-over substrate for UV surface-enhanced resonance Raman scattering at the deepest UV wavelength used to date (λ = 229 nm) [46] has been reported.…”
Section: Aluminummentioning
confidence: 83%
“…Wang et al [45] reported a lifetime reduction of ≈7.2×, exceeding the previously reported value ≈3.5× by Jiao et al [44]. The first fabrication of Al film-over substrate for UV surface-enhanced resonance Raman scattering at the deepest UV wavelength used to date (λ = 229 nm) [46] has been reported.…”
Section: Aluminummentioning
confidence: 83%
“…[25][26][27] All these features are highly appealing to improve the tryptophan autofluorescence detection of single proteins and extend plasmonics into the UV range. [28][29][30] While numerical simulations of plasmonic resonances in aluminum nanoparticles 31,32 and nanoapertures [33][34][35] predict single emitter fluorescence enhancement, the experiments on UV plasmonics have remained largely focused on dense molecular layers deposited on nanoparticle arrays to enhance Raman scattering, [36][37][38][39] or fluorescence. [40][41][42][43] Metal nanoapertures were shown to reduce the fluorescence lifetime, 44,45 but there has been no report so far quantifying the plasmonic-enhanced UV fluorescence at the single protein level.…”
mentioning
confidence: 99%
“…5 As most organic molecules feature strong absorption bands in the UV spectral domain, extending plasmonics into the 200-400 nm ultraviolet range is of major interest to further promote sensing and catalysis applications. [6][7][8][9] However, gold and silver, the classical metals used for plasmonics in the visible and near-infrared spectral ranges, fail to operate in the UV regime due to their strong losses and interband transitions below 400 nm. Currently aluminum is the most widely used metal for UV plasmonics, 10,11 owing to its good optical properties down to 200 nm, low cost and CMOS compatibility.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] However, while many theoretical works have outlined the high potential of aluminum for UV plasmonics, 13,[35][36][37][38] the aluminum applications operating in the 200-400 nm UV range remain scarce, and are often limited to evaporated samples or non-aqueous solvents. [7][8][9][39][40][41][42][43] A largely overlooked issue limiting the use of aluminum for plasmonics is corrosion in water environment. 16,30 While aluminum is quite stable in air due to its natural oxide layer, it can corrode when exposed to water medium.…”
Section: Introductionmentioning
confidence: 99%